A new approach to rectangle intersections: Part II - Edelsbrunner, Herbert (International journal of computer mathematics, 1983)
The study begun in Part I is completed by providing an algorithm which reports all intersecting pairs of a set of rectangles in d dimensions. This approach yields a solution which is optimal in time and space for planar rectangles and reasonable in higher dimensions.